Optimization of the Coagulation–Flocculation Process for Slaughterhouse Wastewater Using Response Surface Methodology. Issue 7 (12th July 2020) - Gökçek, Öznur Begüm; Özdemir, Safiye
Abstract: Slaughterhouse wastewater is one of the main sources of environmental pollutants, containing a high amount of organic matter (chemical oxygen demand (COD), biochemical oxygen demand (BOD)), total nitrogen (TN), total suspended solids (TSS), total phosphorus (TP), grease, and oil. The main aim of the present research is optimizing the coagulation–flocculation process and examining the effects of experimental factors with each other, for example, pH, the concentration of two different coagulants (FeCl3 and alum), rapid mixing rate, and settling time. Therefore, it is aimed to treat slaughterhouse wastewater using the coagulation–flocculation process with the optimization of the response surface methodology (RSM). COD, turbidity, and suspended solids (SS) of the treated wastewater are chosen as the response variables. Furthermore, the optimal conditions for three responses are acquired by employing the desirability function approach. When the experimental results of two coagulants are compared, it is observed that the alum coagulant gave better results for the three responses. The alum coagulant utilized in the present research is able to increase COD, SS, and turbidity removal efficiency by 75.25%, 90.16%, and 91.18%, respectively. It is possible to optimize coagulation–flocculation by utilizing the RSM analysis, which proves that coagulation can pre‐treat slaughterhouse wastewater. Abstract : Coagulation and flocculation for wastewater treatment represent tested ways to improve efficiency and to remove a high volume of particles. This study presents the optimization of the coagulation–flocculation process by RSM for slaughterhouse wastewater and the investigation of the interactive impacts of experimental factors. Here, three different responses (COD, turbidity, and SS removal) using real wastewater are investigated.